Comparison of PCR and Viable Count as a Method for Enumeration of Bacteria in an A/J Mouse Aerosol Model of Q Fever - Hartley, M. Gill; Ralph, Esther; Norville, Isobel H.; Prior, Joann L.; Atkins, Timothy P. (Frontiers in Microbiology, 2019)
Historically, disease progression in animal models of Q fever has been carried out using PCR to monitor the presence of Coxiella burnetii DNA in the host. However, the colonisation and dissemination of other bacterial infections in animal models is tracked using viable counts, enabling an accurate assessment of bacterial load within tissues. Following recent advances in the culture methods for C.burnetii, with the development of ACCM-2, it has become possible to monitor the pathogenesis of C. burnetii in a host by direct culture. Here we compare and contrast the different information gained by using PCR or viable counts to study this disease.